THE HISTORICAL MONUMENTS, ANCIENT PLACES, GREAT FIGURES AND MUSEUMS OF THE COUNTRY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract encapsulates the diverse cultural heritage of Uzbekistan, highlighting its historical monuments, ancient cities, revered figures, museums, traditional crafts, culinary delights, festivals, and modern cultural revival. Uzbekistan's rich tapestry of history is depicted through its UNESCO World Heritage Sites like Samarkand and Bukhara, alongside the legacy of figures such as Amir Timur and Al-Biruni. The country's museums serve as guardians of its past, while traditional crafts like suzani embroidery and culinary delights like plov showcase its living traditions. Festivals such as Navruz and the Silk and Spices Festival bring communities together in celebration. Uzbekistan's cultural landscape is evolving with modern influences, seen notably in Tashkent's contemporary art scene. Efforts to promote cultural exchange and preserve intangible heritage highlight the enduring spirit of Uzbekistan's people and their commitment to celebrating diversity and tradition. This abstract invites readers to explore Uzbekistan's enchanting cultural heritage, which serves as a bridge between the country's illustrious past and vibrant present.